Optimal Freshness Crawl Under Politeness Constraints - Kolobov, Andrey; Peres, Yuval; Lubetzky, Eyal; Horvitz, Eric (SIGIR 2019, 2019)
A Web crawler is an essential part of a search engine that procures information subsequently served by the search engine to its users. As the Web is becoming increasingly more dynamic, in addition to discovering new web pages a crawler needs to keep revisiting those already in the search engine's index, in order to keep the index fresh by picking up the pages' changed content. Determining how often to recrawl pages requires making tradeoffs based on the pages' relative importance and change rates, subject to multiple resource constraints — the limited daily budget of crawl requests on the search engine's end and politeness constraints restricting the rate at which pages can be requested from a given host. In this paper, we introduce PoliteBinaryLambdaCrawl, the first optimal algorithm for freshness crawl scheduling in the presence of politeness constraints as well as non-uniform page importance scores and the crawler's own crawl request limit. We also propose an approximation for it, stating its theoretical optimality conditions and in the process discovering a connection to an approach previously thought of as a mere heuristic for freshness crawl scheduling. We explore the relative performance of PoliteBinaryLambdaCrawl and other methods for handling politeness constraints on a dataset collected by crawling over 18.5M URLs daily over 14 weeks.